Y-intercept happens at x=0. Plug that into the equation. you'll get the y-intercept happens at (0,6). Then, to find the x-intercept y=0. Plug that into the equation. You'ff find that the x-intercept happens at (-9,0)
f(x)=4x^3 - 6x^2 + 2x - 5
f(-2)
Replace X with -2:
4(-2)^3 - 6(-2)^2 + 2(-2) - 5 =
Calulate the powers:
4(-8) - 6(4) +(-4) -5=
Multiply:
-32 - 24 -4 -5=
Subtract
-65
Answer:
P(G)= 7/10
B, 1, P(not B)
1- 8/10, p(Y)= 2/10
Step-by-step explanation:
hope this helps
correct me if this is wrong
Answer:
<em>f(x)=x²-3x-10</em>
Step-by-step explanation:
\begin{gathered}f(x) = x {}^{2} - 3x - 10 \\ to \: find \: x \: intercept \:o r \: zero \: substitute \: f(x) = 0\: \\ 0 = x {}^{2} - 3x - 10 \\ x {}^{2} - 3x - 10 = 0 \\ x {}^{2} + 2x - 5x - 10 = 0 \\ x(x + 2) - 5x - 10 = 0 \\ x(x + 2) - 5(x + 2) = 0 \\ (x + 2).(x - 5) = 0 \\ x + 2 = 0 \\ x - 5 = 0 \\ x = - 2 \\ x = 5\end{gathered}
f(x)=x
2
−3x−10
tofindxinterceptorzerosubstitutef(x)=0
0=x
2
−3x−10
x
2
−3x−10=0
x
2
+2x−5x−10=0
x(x+2)−5x−10=0
x(x+2)−5(x+2)=0
(x+2).(x−5)=0
x+2=0
x−5=0
x=−2
x=5
therefore the zeros of the equation are x₁=-2,x₂=5